Multimodality imaging for transcatheter tricuspid valve repair and replacement - Tomlinson, Stephen; Rivas, Carlos Godoy; Agarwal, Vratika; Lebehn, Mark; Hahn, Rebecca T. (Frontiers in Cardiovascular Medicine, 2023)
Transcatheter tricuspid intervention is a rapidly evolving field with multiple classes of therapeutic devices currently in development. Procedural success in tricuspid intervention is predicated on appropriate device selection for patient specific anatomy and satisfactory imaging for intra-procedural guidance. This review will outline protocols and methodology for multi-modality imaging assessment of the tricuspid valve and associated structures, with emphasis on anatomic and functional characteristics that determine suitability for each class of tricuspid intervention. Intra-procedural imaging requirements for each class of device, with design and procedural imaging guidance of specific devices, will also be addressed.